Stability Analysis of Double Axis Retractable Solar Panel Mechanism for Harbour Tug Application - Danang Cahyagi; Sapto Wiratno Satoto; Ihsan Musyary; Haris Susmana; Ranjit; Wanda Cantika Putri; Muhammad Regie (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Due to the use of fossil fuels in recent decades, maritime researchers and stakeholders have started to become concerned about energy efficiency and environmental protection. The larger social and economic facets of society may suffer as a result of these problems. In an effort to offer a remedy, this research created the B-Solar Wings, the double axis retractable solar panel mechanism design concept for harbor tug applications. B-Solar Wings was created using a variety of strategies to make the most of harbour tugs' constrained space for solar energy absorption while taking into account challenging ergonomic and safety concepts. B-Solar Wings can assemble 7 solar panel units for a total power of 3150 based on the design results. In order to assess the viability of stability brought on by the installation and use of solar panels, this study also offers a modeling analysis. The B-Solar Wings are stable in terms of stability, according to the results of the modeling and validation with the guidelines stated in IMO A. 749 (18). The minimum required value for one of the categories, code 3.1.2.1: Area 0 to 30, is 3.15 m.deg, and the harbour tug's stability value is 17.11 m.deg in the folded position and 17.10 m.deg in the full-open position. Solar energy produced by solar panels can be stored in a battery and integrated into the main distribution panel through multiple stages of voltage conversion and stabilization in the power system for B-Solar Wings.